Condom use errors and problems in a national sample of young Croatian adults - Baćak, Valerio (Array, 2012)
In this study, we examined the correlates of condom use errors and problems in a population-based study conducted in 2010 among young Croatian adults aged 18-25 years. Out of a total sample of 1, 005 participants, 679 reported condom use in the preceeding year. The analyses focused on four outcomes: condom breakage, condom slippage, condom-related erection loss, and delayed condom application. Eighteen percent of participants experienced breakage, 13% reported slippage, 17% reported erection loss, and 34% applied a condom after intercourse started. Multivariate logistic regression analyses were performed to examine the correlates of these condom use errors and problems. Condom breakage was less likely to be reported by women and older participants. The odds of breakage were increased for participants who reported being under the influence of drugs during sex and who reported other condom use errors and problems in the past year. Condom slippage was more likely to appear among younger participants and those who reported condom breakage and delayed condom application. Condom-related erection loss was positively associated with a higher number of sexual partners in the preceeding year, condom breakage, and a higher score on the Anti-Erotic Obstacles to Condom Use Scale. Odds of delayed condom application were increased for participants who experienced condom breakage and for those who consumed alcohol before sex in the past year. Having used a condom at first sex significantly reduced the odds of applying a condom after intercourse started. In comparison to non-habitual condom users, habitual users were found less likely to report any of the assessed condom-use errors and problems. Improving condom use skills remains an important task in Croatia, which is currently hampered by the absence of the evidence-based sex education in schools.